Larval preference and performance of the green lacewing, Plesiochrysa ramburi (Schneider) (Neuroptera: Chrysopidae) on three species of cassava mealybugs (Hemiptera: Pseudococcidae) - Sattayawong, Charida; Uraichuen, Sopon; Suasa-ard, Wiwat (Agriculture and Natural Resources, 2016)
The green lacewing, Plesiochrysa ramburi (Schneider) (Neuroptera: Chrysopidae), is a dominant predatory insect in cassava fields. The suitability of different cassava mealybug species as prey for Pl. ramburi is important information for mass rearing in the laboratory. Phenacoccus manihoti Matile-Ferrero, Phenacoccus madeirensis Green and Pseudococcus jackbeardsleyi (Gimpel & Miller) were compared to determine their potential as prey for Pl. ramburi larvae by testing the green lacewing’s preference and performance. Non-choice tests showed that Pl. ramburi larva could feed on all three cassava mealybug species. Choice tests showed that the 1st and 2nd instars of Pl. ramburi preferred Ph. manihoti and the 3rd instars preferred Ph. madeirensis. However, life table parameters showed that the highest net reproduction number (19.1967) and gross reproductive rate (46.0156, females/female/generation) occurred when Pl. ramburi fed on Ps. jackbeardsleyi. This indicates that Ps. jackbeardsleyi is the most suitable diet for the mass rearing of Pl. ramburi to allow releases in integrated pest management programs.